(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The importance of studying the health status of higher education students is due to modern problems in the field of physical education and sports. In conditions of intensive academic load, stress and irregular physical activity, the problem of maintaining the health of students becomes especially relevant. Sport, as an important element of physical culture, can significantly improve the functional state of the body, increase physical endurance and strengthen the immune system. However, to assess the real impact of sports loads on human health, comprehensive monitoring is necessary, which includes physiological, psychophysical and social aspects. Scientific research in this field is of great importance for the development of the physical education system, for the formation of a healthy lifestyle among students and the creation of effective methods of prevention and correction of diseases. Monitoring the health status of students involved in sports allows us to more accurately take into account the individual characteristics of the body and provide optimal conditions for the development of the physical capabilities of young people. The study was conducted at the Department of Physical Culture, Sports and Health of Lutsk National Technical University. 60 male applicants participated in the study. The age of the young men was 18-19 years. The applicants were divided into three groups: Group 1 - young men who do not play sports, but attend physical education classes during the academic year (20 people); Group 2 - applicants who attend the volleyball section (20 people); Group 3 - young men who are involved in athletics (middle-distance running) (20 people). Thus, the study of the health status of applicants of different groups of higher education institutions is relevant and important for the formation of a healthy lifestyle, disease prevention, development of effective physical education programs and improving the general health of young people.